Studying Early Brain Development: Educators' reports about their Learning and its Applications to Early Childhood Policies and Practices. Issue 3 (September 2015) - Diamond, Alexandra; Whitington, Victoria
THE UNIVERSITY OF SOUTH Australia's online course 'Brain development in the Early Years' is a response to Mustard's Thinker in Residence Report (2008) which recommended the early childhood educator workforce acquire knowledge about young children's brain development. This research investigated educators' views on the value for their work of learning about early brain development. Data comprised responses to course content in online course discussions and a standard anonymous online course evaluation instrument, written by 45 in-service and pre-service educators enrolled in the course. Analysis revealed four themes regarding educators' statements about the value of brain development knowledge for their roles as educators: 'Working with families', 'Working with children', 'Advocacy' and 'Working across services'. Themes are described and illustrated with examples from students' writing. Findings are discussed in terms of the impact of educators' knowledge about brain development on their thinking about their professional practice.